Game Edukasi 3D Teknik Bercocok Tanam Secara Hydroponic Dengan Pendekatan Adaptive Learning - Raditya Danar Dana; Dita Rizki Amalia; Martanto Martanto (STMIK IKMI Cirebon, 2019)
The yard can be optimized to fulfill family consumption needs independently. Hydroponic farming techniques are very suitable to be developed on limited land. However, not many people use the yard to fulfill household consumption needs, this is due to the lack of community knowledge about hydroponic farming techniques. In order to improve the understanding of planting techniques with hydroponic techniques, this research will develop interactive learning media based on 3D games using the ADDIE system development method. Meanwhile, the Sugeno model is used to implement the adaptive quiz feature. Development of 3D Educational Games provides an alternative way to learn Hydroponic farming techniques in a fun way through learning methods while playing through the adaptive learning approach and simulation features provided. The level of compatibility of the behavior of the questions with the fuzzy rules set in Fuzzy Rules produces 80% accurate performance.